Dielectric relaxation and microwave absorption properties of aurivillius-type multiferroic ceramics. Issue 8 (1st June 2018) - Sun, Shujie; Chen, Wenjin; Fang, Liang; Cheng, Nian; Xiao, Zhenyu; Zhao, Zhiqiang; Tian, Yongshang; Lu, Yalin
Abstract: Aurivillius-type multiferroic oxides are increasingly being studied for potential application in multifunctional areas because of their feasible platforms incubating photonic, electric, magnetic, etc. properties. Here, we report the original observations of the dielectric relaxation, electromagnetic properties and high-performance microwave absorption of the single-phase Aurivillius-type ceramics. Two thermally activated relaxation processes were determined by the frequency-dependent behaviour of the dielectric loss peak at low and high temperatures. The complex permittivity and permeability were measured at frequencies 2–18 GHz and the microwave attenuation performances were calculated from the experimentally determined electromagnetic parameters. Significantly, the damped dielectric and magnetic resonances were clearly observed at 12–14 GHz and the excellent microwave absorption properties were presented for the first time and are sensitive to the sample thickness. The minimum reflection loss (RL) surpasses − 30 dB at different thicknesses. Especially, the minimum RL reaches − 70.1 dB at 13.2 GHz and the absorption bandwidth (RL≤ −20 dB) is close to 12 GHz (5.7–17.7 GHz). This work opens up a new pathway to develop Aurivillius-type multiferroic oxides in electromagnetic wave attenuation materials.